Pendampingan dalam Memasarkan Produk Hasil Usaha UKM melalui Penggunaan Media Sosial di Kabupaten Gunung Mas Kalimantan Tengah - Luluk Tri Harinie; Alexandra Hukom; Juma’eh Juma’eh (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
The purpose of this Community Service or Pengabdian kepada Masyarakat (PKM) activity was to improve the capabilities and skills of the marketing aspects of business products, especially with regard to the ability and skills to create business product promotions using online media. The results of these tools will later be shared through the chat application on Social Media with web.whatsapp.com in order to improve business. Therefor, it can expand the area of ​​marketing the results of business products with a relatively faster and cheaper cost, even without promotion cost at all. The implementation of activities was in Gunung Mas Regency, Central Kalimantan Province, involving 6 SMEs who became PKM Partners. The method of carrying out activities was by directly visiting the business locations of each PKM partner for socialization activities, training, mentoring and discussing, and evaluation monitoring. The result indicated that PKM Partners became skilled at promoting business products as well as able to also promote through chat applications on social media by web.whatsapp.com.